2020
DOI: 10.1097/01.aoa.0000693676.83300.41
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Drug-related Death and Suicide are Leading Causes of Postpartum Death in California

Abstract: (Am J Obstet Gynecol. 2019;221:489.e1–489.e9) Efforts to reduce maternal mortality has become a priority worldwide and in the United States. In 2018, the Preventing Maternal Deaths Act was enacted to support state efforts to track and review maternal deaths. Also, targeted action plans and safety bundles for clinical care that focus on common causes of maternal mortality have been developed. Yet, there is limited evidence on the impact that drug-related deaths and suicide have on postpartum women. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Depending on the measurement scale, some authors have reported up to one‐third of women presenting high levels of depression symptomatology 1 . A recent population‐based cohort study has shown suicide to be a major contributor to mortality in the postpartum period 2–4 . Preterm births have been documented as presenting a risk for post‐traumatic stress disorder (PTSD), acute stress disorder, depression and anxiety for parents (mothers in particular) compared with full‐term births 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the measurement scale, some authors have reported up to one‐third of women presenting high levels of depression symptomatology 1 . A recent population‐based cohort study has shown suicide to be a major contributor to mortality in the postpartum period 2–4 . Preterm births have been documented as presenting a risk for post‐traumatic stress disorder (PTSD), acute stress disorder, depression and anxiety for parents (mothers in particular) compared with full‐term births 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Palladino et al 26 reported that prenatal and postpartum suicide disproportionately affects AI/AN and white women, yet, others report little or no risk for AI/AN women. 20,21,[23][24][25]27 This result could be explained partially by the use of an ''Other'' race/ethnicity category; Palladino et al was the only study that reported AI/AN women as AI/AN versus ''Other. ''…”
Section: Resultsmentioning
confidence: 99%
“…21 Suicide rates for ''Other'' women (an unknown portion of which were AI/AN) ranged from 0% to 13.3%. 20,23,24,27,28,38 Substance use. We found no studies examining AI/AN pregnancy-associated maternal mortality from substance use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who consider, attempt, and/or carry out suicide often have recent interactions with health care providers before their deaths. 43 In 2018, ACOG published updated clinical guidance for women's health providers to screen patients at least once during the perinatal period for depression and anxiety using standardized, validated tools. During postpartum visits, more extensive emotional health assessments and referrals may be indicated.…”
Section: Intimate Partner Homicide and Pregnancymentioning
confidence: 99%